PENGARUH HARGA, PROMOSI, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA TOSERBA MBANGI MART WOROMARTO PURWOASRI - Diah Ayuningtyas; Eko Widodo; Aprilia Dian Evasari (Cahaya Ilmu Bangsa, 2024)
This research was conducted with the aim of fulfilling, explaining, and proving the hypothesis that price, promotion, and product quality have an impact on purchasing decisions at Toserba Mbangi Mart Woromarto Purwoasri. The research method used is quantitative, where the sampling method is accidental sampling using a questionnaire and a Likert scale. The population of this research is all consumers of Toserba Mbangi Mart Woromarto Purwoasri, which is unknown. The sample for this research consists of 385 respondents using the Cochran formula. The analysis method used is multiple linear regression using SPSS 25 for Windows. This research shows that the variables of price (X1), promotion (X2), and product quality (X3) have a partial effect on purchasing decisions (Y) at Toserba Mbangi Mart. The price has a significance value of 0.000 < 0.05 and t calculated > t table, which is 11.786 > 1.966. Promotion has a significance value of 0.000 < 0.05 and t calculated > t table, which is 11.188 > 1.966. Product quality has a significance value of 0.000 < 0.05 and t calculated > t table, which is 6.841 > 1.966. All three variables also have a simultaneous effect on purchasing decisions with a significance value of 0.000 < 0.05 and F calculated > F table, which is 641.346 > 2.628.